Is social inclusion of workforce in Colombia in counter of what sustainability means? (2015)
This article demonstrates through analysis of official data that in Colombia there are considerable differences regarding to social inclusion of its productive system employees, based on a framework that considers employment quality as an axe of corporate sustainability and object of social responsibility policies. Conclusions provide evidence to affirm that people with employments of inferior quality are the most excluded due to the consequences of a persistent labor scarcity in the country. The situation suggests that the Colombian business community needs a systematic review of sustainability policies, particularly in relation to the type of employment it is providing, given that work is a highly influential aspect of individuals life